2011
DOI: 10.1038/onc.2011.470
|View full text |Cite
|
Sign up to set email alerts
|

Myc represses miR-15a/miR-16-1 expression through recruitment of HDAC3 in mantle cell and other non-Hodgkin B-cell lymphomas

Abstract: Our recent study demonstrated miR-15a/16-1 downregulation in mantle cell lymphoma (MCL). Here, we investigated mechanisms of miR-15a/16-1 transcriptional repression and its epigenetic regulation by c-Myc and histone deacetylase (HDAC) in MCL. c-Myc expression was detected in MCL cell lines and in the primary MCL samples, and pri-miR-15a/16-1 mRNAs were significantly upregulated in Mino and Jeko-1 cells with c-Myc knockdown by small interfering RNAs (siRNAs). Our co-immunoprecipitation analysis showed that c-My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
119
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 28 publications
(39 reference statements)
11
119
1
Order By: Relevance
“…Conversely, we demonstrate that miR-548m regulated c-Myc expression through direct targeting of c-Myc 3′-UTR and downregulation of miR-548m, in turn, contributes to c-Myc overexpression, thus generating a positive c-Myc/miR-548m feedback loop to ensure persistent high protein levels of c-Myc and further repression of miR-548m expression in lymphoma microenvironment. Moreover, the finding of c-Myc-induced EZH2-mediated miR-548m repression is in line with findings of our previous study that miR-29 expression is c-Myc and EZH2 dependent, implicating a genetic silencing mechanism for c-Myc-induced widespread miRNA repression (20,21,43). JQ1 functions as a specific inhibitor of BET proteins, including bromodomain-containing protein 4 (BRD4) and BRD2 through interference with the acetyl-lysine recognition domains (bromodomains).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Conversely, we demonstrate that miR-548m regulated c-Myc expression through direct targeting of c-Myc 3′-UTR and downregulation of miR-548m, in turn, contributes to c-Myc overexpression, thus generating a positive c-Myc/miR-548m feedback loop to ensure persistent high protein levels of c-Myc and further repression of miR-548m expression in lymphoma microenvironment. Moreover, the finding of c-Myc-induced EZH2-mediated miR-548m repression is in line with findings of our previous study that miR-29 expression is c-Myc and EZH2 dependent, implicating a genetic silencing mechanism for c-Myc-induced widespread miRNA repression (20,21,43). JQ1 functions as a specific inhibitor of BET proteins, including bromodomain-containing protein 4 (BRD4) and BRD2 through interference with the acetyl-lysine recognition domains (bromodomains).…”
Section: Discussionsupporting
confidence: 75%
“…We next investigated the underlying molecular mechanism of stroma-mediated miR-548m downregulation. Our recent studies revealed that c-Myc recruited HDAC3 and EZH2, a histone methyltransferase and a member of the polycomb group of proteins, to the promoters of miR-29 and miR-15a/16 as corepressors to downregulate miRNA expression (20,21). We, thus, tested whether miR-548m expression is c-Myc dependent and its repression is mediated through histone modification.…”
Section: Cell Adhesion To Stromal Cells Induces Hdac6 Expression and mentioning
confidence: 99%
“…Very few direct interactions between transcriptional regulators and pri-miRNAencoding genes have been reported in plants or other organisms. In animals, there are some reports of transcription factors directly associating with pri-miRNA genes and resulting in the expression or repression of the associated genes (Hino et al, 2008;Xiong et al, 2009;Zhou et al, 2010;Zhang et al, 2012b). In Arabidopsis and other angiosperms, miR156 and miR172 are regulators of phase transitions, with miR156 delaying phase transitions while miR172 promotes the progression through the life cycle (for review, see Huijser and Schmid, 2011).…”
Section: Fus3 and Genes Regulated In Response To Supraoptimal Temperamentioning
confidence: 99%
“…HDAC complexes mediate repression of miR-15a, miR-16, and miR-29b in CLL and in NHL. 104,105 Treatment with HDACi induced the expression of these miRNAs, antagonizing survival protein MCL-1 and triggering cell death. 104 Deregulated PRC2 complexes repress miR-31 in adult T-cell leukemia and lead to activation of NF-kB, triggering oncogenic signaling.…”
mentioning
confidence: 99%